Inhibitors of the RBD-ACE-2 Found among a Wide Range of Dyes by the Immunoassay Method - Ekaterina D. Mordvinova; Polina A. Nikitina; Olga I. Yarovaya; Ekaterina A. Volosnikova; Denis E. Murashkin; Anastasiya A. Isaeva; Tatiana Y. Koldaeva; Valery P. Perevalov; Nariman F. Salakhutdinov; Dmitriy N. Shcherbakov (Chemosensors, 2023)
Angiotensin-converting enzyme 2 (ACE2), the functional receptor of SARS-CoV-2, plays a crucial role in the pathogenesis of COVID-19. ACE2 targeting holds the promise for preventing and inhibiting SARS-CoV-2 infection. In this work, we describe the development and use of a test system based on competitive ELISA for the primary screening of potential antiviral compounds. We studied the activity of the library of dyes of different groups. Several dyes (ortho-cresolphthalein, eosin (free acid), eosin (Na salt)) that inhibited the interaction of ACE2 with the spike proteins of SARS-CoV-2 have been identified among the candidates. A potential antiviral drug, methylene blue, did not show activity in our study. We believe that our results can help in the further search for inhibitors of interaction between the coronavirus spike protein and ACE2 receptor.